Brain drain or brain circulation: exploring scholar views on working abroad in the era of global mobility - Cahyani, Adriyanti Regita; Novia, Rita Three; P, Cyndika Galeh P; Puspitasari, Fantika Febry (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3748, 2025)
This study seeks to understand the causes and obstacles faced by graduates in the context of brain drain and brain circulation among alumni of Maulana Malik Ibrahim State Islamic University Malang. Brain drain describes the migration of educated people to other places, both regions and countries, due to better job opportunities and quality of life. This study uses a descriptive quantitative approach by collecting data through questionnaires distributed to 100 alumni from various faculties in 2025. The data were analyzed using IBM SPSS Statistics software with descriptive analysis methods. The findings show that the driving and restraining factors have a significant impact on graduate mobility, with averages of 3.69 and 3.85 (high category), respectively. The main driving factors consist of limited research facilities and career opportunities, while the restraining factors mainly include attractive financial income and international meetings. The study concluded that the brain drain phenomenon can be transformed into brain circulation if there are policies that strengthen research and involve alumni globally.